(Re)visiting the neighbourhood. Issue 12 (15th November 2021) - Drozdzewski, Danielle; Webster, Natasha A.
Abstract: Neighbourhoods are complex places, at once familiar and foreign, easily found on a map or bounded by rules only insiders know. Although neighbourhood is a concept, one that we experience daily, it remains conceptually challenging for geographers and planners alike. Nevertheless, and despite its complexity, the importance of the understanding the neighbourhood should not be overlooked, especially in the post‐pandemic world. Understanding the neighbourhood as a concept, place and context, poses opportunities for geographers to think‐with and think laterally across the demographic information we may have on who lives in a neighbourhood, and towards the integration of lived experiences to our explorations of it. In this paper, we critically review key literature on the neighbourhood since 2015, and discuss recurrent themes from that scholarship: belonging, place attachment, everyday interactions, and spatial formations. We argue that the neighbourhood be considered as a multilayered locale and a site imbued with emotions and meanings located with, in and stemming from place‐specific conceptual, temporal, and spatial contexts of the neighbourhood. Our (re)visit of the neighbourhood occasions, we think, an opportunity for geographers to keep in touch with the neighbourhood and shape new discussions around these important 'lived in' spaces and places.